9,9-Bis[4-(2-chloroethoxy)phenyl]-9H-fluorene - Shah, K.; Raza Shah, M.; Khan, I. U.; Ng, S. W. (International Union of Crystallography, 2010)
The title compound, C29H24Cl2O2, a fluorene derivative, features a C atom that is connected to four phenylene rings, two of which are almost coplanar (r.m.s. deviation = 0.035 Å) as they belong to the fluorene system. The other two rings are aligned at angles of 67.5 (5) and 85.5 (5)° with respect to the pair. The O and Cl atoms of the –OCH2CH2Cl– units adopt a gauche conformation [torsion angles = 61.6 (6) and 66.6 (5)°].